2021
DOI: 10.1111/jop.13156
|View full text |Cite
|
Sign up to set email alerts
|

circBICD2 targets miR‐149‐5p/IGF2BP1 axis to regulate oral squamous cell carcinoma progression

Abstract: Background Circular RNAs (circRNAs) are related to oral squamous cell carcinoma (OSCC) progression. circRNA bicaudal D cargo adaptor 2 (circBICD2) has been reported to be abnormally expressed in OSCC. However, the function and mechanism of this circRNA in OSCC progression remain largely unknown. Methods circBICD2, microRNA‐149‐5p (miR‐149‐5p), and insulin‐like growth factor 2 mRNA‐binding protein 1 (IGF2BP1) abundances were examined via quantitative reverse transcription polymerase chain reaction or Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Several studies confirmed that circRNAs were ceRNAs of miRNA. For instance, circBICD2 enhanced IGF2BP1 as ceRNA via miR-149-5p, thus accelerating the proliferation and migration of OSCC cells (28). In addition, overexpressed circPHIP downregulated miR-142-5p and upregulated PHIP and ACTN4, thus aggravating OSCC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that circRNAs were ceRNAs of miRNA. For instance, circBICD2 enhanced IGF2BP1 as ceRNA via miR-149-5p, thus accelerating the proliferation and migration of OSCC cells (28). In addition, overexpressed circPHIP downregulated miR-142-5p and upregulated PHIP and ACTN4, thus aggravating OSCC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Hsa_circRNA_100533 inhibits OSCC development through regulating GNAS by targeting hsa_miR_933 [ 29 ]. CircBICD2 regulates OSCC progression by targeting miR-149-5p/IGF2BP1 [ 30 ]. Based on the crucial role of the circRNA/miRNA/mRNA network in OSCC development, we performed bioinformatics analysis and a serial experiment to demonstrate the underlying mechanisms of circMTO1.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis showed that miR-149-5p could enhance the chemosensitivity of OSCC cells to cisplatin by targeting TGF b2, inhibit cell proliferation, migration and invasion, and promote apoptosis (75). Notably, Qiu et al confirmed that CircBICD2 knockdown could inhibit the proliferation, migration, invasion, glutamine degradation and increase apoptosis of OSCC cells by regulating the miR-149-5p/IGF2BP1 axis (70). Similarly, down-regulation of lncRNA DLEU1 could inhibit the occurrence of OSCC by regulating the miR-149-5p/CDK6 axis (76).…”
Section: Other Cancers Of Digestive Systemmentioning
confidence: 99%
“…In addition to GC, HCC and CRC, miR-149-5p has also been studied in other digestive system cancers, including oral cancer, esophageal cancer and ductal adenocarcinoma of the pancreas (70)(71)(72)(73)(74)(75)(76).…”
Section: Other Cancers Of Digestive Systemmentioning
confidence: 99%